The principle of an effective basis for corporate governance and its impact on enhancing the quality of accounting disclosure Study the direction of some opinions of academics and professionals - safir, mohamed; sahraoui, yassine (Journal of Research in Finance and Accounting, 2019)
This study aims at identifying the impact of corporate governance on the basis of the principle of a strong and effective basis for corporate governance on the quality of accounting disclosure. Where we studied the views of a group of academics and professionals. For this purpose, a questionnaire was prepared, distributed and analyzed using the statistical program (spss). The results of this study have found a strong, effective and positive impact on the application of the principle of an effective and firm basis for corporate governance in finding quality disclosure. The study also found that there is no impact on the application of this principle on the quality of accounting disclosure. The study recommends the application of the principles of corporate governance by providing the legislative and legal framework, in addition to training and rehabilitation of the parties concerned to implement them.